Dissolved Phosphorus Of Phosphate Stones With Ultrasonic Waves As An Efforts - Rahmat Ibnu Mas'ud; Sugeng Triyono; Sri Waluyo; Tamrin - (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2012)
Fertilizer is a material that can add nutrients to soil.  Phosphate is one of essential elements of fertilizer for plants. Ultrasonic waves can potentially be used as a method to dissolve phosphorus from phosphate stone, by means of immersion in water and gived of ultrasonic waves.  The aim of this study was to analyze the P content from phosphate stone that was dissolved in water and the excited by ultrasonic waves.  The tests were the concentration of phosphate in water of 30, 60, and 90%, and the duration of ultrasonic wave (60 kHz) of 15, 30, and 60 minutes.  The parameters observed were the levels of dissolved P (P2O5), pH value, and specific energy. The samples were analyzed, namely liquid and solid samples were separated after ultrasonic vibrate. The results of the analysis of the highest levels of soluble P from liquid samples are at 90% concentration, treatment time-vibrate 15 minutes, that is equal to 0.0415 mg/l, whereas the treatment of solid samples at concentrations of 60% , within 15 minutes, amounting to 1.38%.  The measurement results show the solution pH is neutral phosphate after vibrated tend to alkaline with pH values between 7 – 8. Sample concentration of 60% treatment, 15 minutes and 90% concentration, treatment time of 15 minutes is the most efficient, because it uses only the smallest specific energy is 0.15 J/mg and 0.1 J/mg, can produce high levels of dissolved P. Keywords: fertilizer, phosphate stones, ultrasonic, P dissolved.